Ab initio calculation of energy levels for phosphorus donors in silicon - J. S. Smith (Nature Portfolio, 2017)
Abstract The s manifold energy levels for phosphorus donors in silicon are important input parameters for the design and modeling of electronic devices on the nanoscale. In this paper we calculate these energy levels from first principles using density functional theory. The wavefunction of the donor electron’s ground state is found to have a form that is similar to an atomic s orbital, with an effective Bohr radius of 1.8 nm. The corresponding binding energy of this state is found to be 41 meV, which is in good agreement with the currently accepted value of 45.59 meV. We also calculate the energies of the excited 1s(T 2) and 1s(E) states, finding them to be 32 and 31 meV respectively.